BUILDING PARTNERSHIP AND GOOD GOVERNANCE IN CORPORATE SOCIAL RESPONSIBILITY - Heryani Agustina (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2018)
Corporate Social Responsibility (CSR) practice in local area involved three governance components that are local government, private sector and society, so productive and strong partnership among those three components need to be built in order to create good governance in CSR. Partnership and good governance in CSR will create synergy and optimal CSR results, so it supports local government programs to create society prosperity. Some area success in building partnership and good governance in CSR, but there are many areas are failed and involved in corruption case of CSR fund. Building partnership and good governance in CSR is not an easy thing because it faced many obstacles related to basic foundation of partnership and good governance itself.